Pendampingan Asuhan Keperawatan Medikal Bedah pada Pasien dengan Gangguan Sistem Pencernaan: Apendisitis - Iif Taufiq El-Haque; Iis Ismayanti (Yayasan Inspirasi El Burhani, 2022)
Introduction: Appendicitis is a disease of the respiratory system where inflammation is due to infection of the appendix or appendix, this infection will cause several complications if surgery is not immediately taken for treatment, usually an appendectomy is performed to reduce the risk of perforation. Appendicitis can be caused by predisposing factors such as obstruction of the lumen, infection with bacteria from the colon (E. Coli, Streptococcus), and male sex in adolescents-adults. As well as precipitating factors such as blockage of the appendix lumen, erosion of the appendix mucosa, and an unhealthy lifestyle, such as eating habits that are low in fiber. Objective: This assistance aims to provide nursing care to the patient Mr. A with a medical diagnosis of appendicitis in the Anggrek room at RSUD Kota Banjar in 2022. Method: Assistance activities are carried out by providing nursing care through 5 stages of the nursing process, including Assessment, Diagnosis, Nursing Intervention, Nursing Implementation, and Evaluation. Result: The results showed that the patient's main complaint was pain in the post-operative appendectomy wound in the right lower quadrant of the abdomen, the diagnosis that appeared in the patient was acute pain and sleep disturbances, after being given nursing actions from January 4-6, the results showed that the patient said the pain he felt has decreased, the patient does not look grimacing, the patient's expression looks relaxed, the pain scale has decreased from the initial scale of 6 to a scale of 3. Conclusion: After the process of providing nursing care was carried out on 04-January-2022, it was found that the nursing problem in Mr. A with a medical diagnosis of appendicitis could be resolved.